Why Don't You Tell Me What I Need to Know? Self-Flipped Classroom and Students' Personal Epistemology - Daniels, Mats; Cajander, Asa; McDermott, Roger; Vasilcheko, Anna; Golay, Diane (Proceedings - Frontiers in Education Conference, 2021)
This is a full research paper addressing the crucial element of understanding students when creating learning environments. It is for instance important to be aware of how students appreciate our way of teaching and to consider consequences of students not understanding or plainly disliking a setup. This paper addresses the negative experiences of students in a peer-learning environment named the self-flipped classroom. Through the lens of a theory of personal epistemology we investigate course evaluation reports and observations from anonymous students. Results indicate that the personal epistemology framework indeed gives some answers to students disliking the self-flipped aspect of the course, and that some students would rather be told what to learn in detail as in the quote: "why don't you tell me what I need to know?". Finally the paper presents some ideas on ways forward.